Les lettres de Lord Chesterfield : decency, ou salvation by « Les Grâces » - Thierry Labica (Revue LISA)
This contribution explores the notion of « decency » in Lord Chesterfield’s letters to his son. Against the familiar assumption that decency is an inherently English disposition, the discussion first introduces Chesterfield as G Orwell’s inverted image. The study of Chesterfield’s decency proceeds to look at six characteristic features of the notion which is seen to contain an admonition to depart from Englishness. The resulting departure from the (English) particular in the direction of the (gallocentric) universal involves a historical bifurcation between earlier expectations of ‘decent’ outward manifestations of (ciceronian or Christian) inwardness and the sheer social gymnastics of dissimulation. The discussion ultimately offers a Marxian interpretation of this version of decency now set against the dual horizon of commodity relations and human perfectibility, and concludes with Chesterfield’s negative invention of a territory of inward intimacy now left to be recaptured by later romantic and nationalistic nostalgias.